Robust control applications for smart truss structure - Carvalhal, Ricardo [UNESP]; Da Silva, Samuel [UNESP]; Júnior, Vicente Lopes [UNESP] (My University, 2005)
A finite element modeling of an intelligent truss structure with piezoelectric stack actuators for the purpose of active damping and structural vibration attenuation is presented. This paper concerns with the following issues aspects: the design of intelligent truss structure considering electro-mechanical coupling between the host structure and piezoelectric stack actuators; the H 2 norm approach to search for optimal placement of actuators and sensors; and finally some aspects in robust control techniques. The electro-mechanical behavior of piezoelectric elements is directly related to the successful application of the actuators in truss structures. In order to achieve the desired damping in the interested bandwidth frequency it is used the H ∞ output feedback solved by convex optimization. The constraints to be reached are written by linear matrix inequalities (LMI). The paper concludes with a numerical example, using Matlab and Simulink, in a cantilevered, 2-bay space truss structure. The results demonstrated the approach applicability.
Keywords: Active damping; Actuators and sensors; Bandwidth frequency; Control applications; Control techniques; Electro-mechanical; Finite element modeling; Host structure; Intelligent truss structure; MATLAB and SIMULINK; Numerical example; Optimal placements; Output feedback; Piezoelectric elements; Piezoelectric stack actuators; Space truss structure; Structural vibrations; Truss structure; Buckling; Convex optimization; Damping; Exhibitions; Linear matrix inequalities; Piezoelectricity; Robust control; Structural dynamics; Piezoelectric actuators